Incidence of carbapenem-resistant Enterobacteriaceae in the multidisciplinary pediatric hospital - L.G. Boronina; E.V. Samatova; S.M. Blinova; M.P. Kukushkina; S.A. Panova; S.S. Ustyugova (LCC «Medicine-Inform», 2020)
L.G. Boronina1,2, E.V. Samatova2, S.M. Blinova1, M.P. Kukushkina2, S.A. Panova2, S.S. Ustyugova2 1Ural State Medical University, Ekaterinburg, Russian Federation 2Regional Children's Clinical Hospital, Ekaterinburg, Russian Federation Aim: to define the incidence of carbapenem-resistant Enterobacteriaceae in the bioassay of hospitalized children. Patients and Methods: From January to December 2019, 940 strains of gram-negative bacteria were isolated from clinical material of 900 patients. Antibiotic susceptibility testing was conducted using the disk diffusion method; SENSITITRE and Phoenix M50 analyzers used «CHROMagarTM KPC» medium. Also, Carbapenem Inactivation Method was used to detect the carbapenemase activity. Results: the species composition of carbapenem-resistant Enterobacteriaceae included: Pseudomonas aeruginosa (n=55), Acinnetobacter baumannii (n=22), Escherichia coli (n=2), Klebsiella pneumoniae (n=40), Klebsiella oxytoca (n=1), Enterobacter cloacae (n=7), Serratia marcescens (n=2), Proteus mirabilis (n=2), Pseudomonas putida (n=1). 12.1% of all Enterobacterales isolates and 29.4% Klebsiella pneumoniae strains were resistant to ertapenem; 17.2% of Enterobacteriaceae and 20% of K. pneumoniae strains were resistant to imipenem and meropenem. 50.9% of Pseudomonas aeruginosa strains were resistant to meropenem and imipenem, and 45% - to doripenem. Acinetobacter baumannii strains resistant to meropenem - 66.6%, imipenem - 63.6%, doripenem - 83.3%. In 30.4% of P. aeruginosa and A. baumannii strains, carbapenemase activity was not detected, which indicated other mechanisms of resistance to carbapenem. Conclusion: in most cases, phenotypic methods only allow to suspect the presence of certain mechanisms of acquired resistance. However, since the main, most common mechanism is the production of hydrolytic enzymes, the identification of mechanisms of resistance to carbapenems should be precisely directed at this. At present, in addition to phenotypic methods, it is optimal to use molecular methods, in particular, real-time PCR, to effectively monitor the distribution of carbapenemase producers. Keywords: Enterobacterales, non-fermenting gram-negative bacteria, carbapenemases, children, infection. For citation: Boronina L.G., Samatova E.V., Blinova S.M. et al. Incidence of carbapenem-resistant Enterobacteriaceae in the multidisciplinary pediatric hospital. Russian Journal of Woman and Child Health. 2020;3(4):295-301. DOI: 10.32364/2618-8430-2020-3-4-295-301.